Clashing and Emerging Genres: The interplay of knowledge forms in educational gaming - Thorkhild Hanghøj (Stockholm University Press, 2011)
Based upon a series of design interventions with the educational computer game series Global Conflicts at various secondary schools, this article explores how educational gaming can be understood as a complex interplay between four knowledge forms - i.e. students' everyday knowledge (non-specialised knowledge), the institutionalised knowledge forms of schooling, teachers' subject-specific knowledge (specialised knowledge forms), and game-specific knowledge forms such as professional journalism, which is one of the inspirations for the game scenario. Depending on how the GC series was enacted by different teachers and students, these knowledge forms were brought into play rather differently. More specifically, several students experienced genre clashes in relation to their expectations of what it means to play a computer game, whereas other students experienced emerging genres - e.g. when one student was able to transform the game experience into a journalistic article that challenged her classmates' understanding of journalistic writing.